Analisis dan Perbaikan Usability pada Antarmuka Pengguna Aplikasi Mobile PDAM Surya Sembada Kota Surabaya dengan menggunakan Metode Usability Testing - Tistya Putri Karima; Hanifah Muslimah Az-Zahra; Andi Reza Perdanakusuma (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2019)
One of the objectives of the PDAM Surya Sembada mobile application is to facilitating public in accessing PDAM Surabaya services. However, in reality there are still many users who complained about the ease when accessing various service features in the application. From the findings in PlayStore, it founds any reviews about the navigation of application was not good, and users cant get any successes notifications when the they took an action, which caused the difficulties and confused. These difficulties affect the usability of the application. Testing the usability of an user interface is important to do. The goal is to finding problems taht related to usability, and to measure the extent of the ease of application. There are two stages for testing the usability of PDAM Surya Sembada Surabaya user interface . The first stage aims to digging the usability problems and the solutions which to be used as material for design improvement recommendations. The second stage aims to assess the level of usability of the user interface after making improvements, so the results can be compared with the previous value. After doing the improvements, the usability value of the application interface for Low Digital Skills respondents increased to 64.7825% from the previous value of 20.095%. Meanwhile, for Tech Savvy respondents the usability value also increased to 64.7825% from the previous value of 29.2925%.